(26 intermediate revisions by 2 users not shown)
Line 21: Line 21:
 
</center>
 
</center>
 
----
 
----
 +
===Solution 1===
 +
First of all, the conditional distribution can be written as:
 +
 
<math>
 
<math>
\begin{align*}
 
 
P(X=x|X+Y=n)
 
P(X=x|X+Y=n)
&=\frac{P(X=x, X+Y=n)}{P(X+Y=n)}\\
+
=\frac{P(X=x, X+Y=n)}{P(X+Y=n)}
&=\frac{P(X=x, Y=n-x)}{P(X+Y=n)}
+
=\frac{P(X=x, Y=n-x)}{P(X+Y=n)}
\end{align*}
+
</math>
\begin{align*}
+
 
 +
And
 +
 
 +
<math>
 
P(X=x, Y=n-x)
 
P(X=x, Y=n-x)
&=P(X=x)P(Y=n-x)\\
+
=P(X=x)P(Y=n-x)\\
&=\frac{e^{-\lambda_1}\lambda^x}{x!}\times \frac{e^{-\lambda_2}\lambda^(n-x)}{(n-x)!}\\
+
=\frac{e^{-\lambda_1}\lambda^x}{x!}\times \frac{e^{-\lambda_2}\lambda^(n-x)}{(n-x)!}\\
&=\frac{e^{-(\lambda_1+\lambda_2)}}{x!}
+
=\frac{e^{-(\lambda_1+\lambda_2)}}{x!}
 
\left(
 
\left(
 
\begin{array}{c}
 
\begin{array}{c}
Line 38: Line 43:
 
\right)
 
\right)
 
\lambda_1^x\lambda_2^{n-x}
 
\lambda_1^x\lambda_2^{n-x}
\end{align*}
+
</math>
\begin{align*}
+
 
{P(X+Y=n)}
+
Also
&={\sum_{k=0}^{k=n}P(X=k,Y=n-k)}\\
+
 
&={\sum_{k=0}^{k=n}P(X=k)P(Y=n-k)}\\
+
<math>
&=\frac{e^{-(\lambda_1+\lambda_2)}}{n!}\sum_{k=0}^{k=n}
+
P(X+Y=n)
 +
={\sum_{k=0}^{k=n}P(X=k,Y=n-k)}
 +
={\sum_{k=0}^{k=n}P(X=k)P(Y=n-k)}\\
 +
=\frac{e^{-(\lambda_1+\lambda_2)}}{n!}\sum_{k=0}^{k=n}
 
\left(
 
\left(
 
\begin{array}{c}
 
\begin{array}{c}
Line 49: Line 57:
 
\end{array}
 
\end{array}
 
\right)
 
\right)
\lambda_1^k\lambda_2^{n-k}
+
\lambda_1^k\lambda_2^{n-k}\\
&=\frac{e^{-(\lambda_1+\lambda_2)}}{n!}(\lambda_1+\lambda_2)^n
+
=\frac{e^{-(\lambda_1+\lambda_2)}}{n!}(\lambda_1+\lambda_2)^n
\end{align*}
+
</math>
So  
+
 
\begin{align*}
+
So, we get
P(X=x|X+Y=n) &=  
+
<math>
 +
P(X=x|X+Y=n) =  
 
\left(
 
\left(
 
\begin{array}{c}
 
\begin{array}{c}
Line 61: Line 70:
 
\right)
 
\right)
 
(\frac{\lambda_1}{\lambda_1+\lambda_2})^x(\frac{\lambda_2}{\lambda_1+\lambda_2})^{n-x}
 
(\frac{\lambda_1}{\lambda_1+\lambda_2})^x(\frac{\lambda_2}{\lambda_1+\lambda_2})^{n-x}
\end{align*}
+
</math>
  
 +
===Solution 2===
 +
Let <math>Z=X+Y</math>,
 +
 +
<math>P_Z(k)=P_Z(z=k)=P_Z(x+y=k)\\
 +
=\sum_{i=0}^{k}P(x=i)(y=k-i)=\sum_{i=0}^{k}\frac{\lambda_1^i e^{\lambda_1}}{i!}\cdot\frac{\lambda_2^{k-i}e^{-\lambda_2}}{(k-i)!}
 +
=e^{-\lambda_1-\lambda_2}\cdot \frac{(\lambda_1+\lambda_2)^k}{k!}
 
</math>
 
</math>
 +
 +
Using <math>(a+b)^k=\sum_{i=0}^{k}a^ib^{(k-i)}\cdot \frac{k!}{i!(k-i)!} </math>
 +
 +
Therefore,
 +
 +
<math>
 +
P_{X|Z}(x=k|z=n)=\frac{P(x=k,z=n)}{P(z=n)}=\frac{P(x=k,x+y=n)}{P(z=n)}=\frac{P(x=k,y=n-k)}{P(z=n)}\\
 +
=\frac{\lambda_1^k e^{-\lambda_1}}{k!}\frac{\lambda_2^{n-k} e^{-\lambda_2}}{(n-k)!}\frac{n!}{e^{-\lambda_1}e^{-\lambda_2}(\lambda_1+\lambda_2)^n}
 +
= \frac{\lambda_1^k \lambda_2^{n-k} }{(\lambda_1+\lambda_2)^n}\frac{n!}{k!(n-k)!}
 +
</math>
 +
 +
===Solution 3===
 +
 +
We will view this problem through the lens of Bayes' Theorem. As such, we can write the conditional distribution as
 +
 +
<math>
 +
P(X = x | X+Y = n) = \frac{P(X = x, X+Y = n)}{P(X+Y = n)} = \frac{P(X = x, Y = n - X)}{\sum^n_{k = 0}P(X = k, Y = n - k)}
 +
</math>.
 +
 +
Since <math>X</math> and <math>Y</math> are independent, we can further write
 +
 +
<math>
 +
P(X = x | X+Y = n) = \frac{P(X = x)P(Y = n - X)}{\sum^n_{k = 0}(P(X=k)P(Y = n-k))}
 +
</math>.
 +
 +
Now let us separate the above expression into numerator and denominator. Recalling that <math>X</math> and <math>Y</math> are independent Poisson r.v.s, the numerator is given by
 +
 +
<math>
 +
P(X = x)P(Y = n - X) = \frac{e^{-\lambda_1}\lambda_1^x}{x!}\cdot\frac{e^{-\lambda_2}\lambda_2^{n-x}}{(n-x)!}
 +
</math>.
 +
 +
Multiplying the above by <math>\frac{n!}{n!}</math> gives
 +
 +
<math>
 +
P(X = x)P(Y = n - X) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}{n\choose x}\lambda_1^x\lambda_2^{n-x}
 +
</math>.
 +
 +
Now let us examine the denominator. Again, we make use of the fact that <math>X</math> and <math>Y</math> are independent Poisson r.v.s to write
 +
 +
<math>
 +
\sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \sum^n_{k = 0}\left(\frac{e^{-\lambda_1}\lambda_1^k}{k!}\frac{e^{-\lambda_2}\lambda_2^{n-k}}{(n-k)!}\right)
 +
</math>.
 +
 +
Again, we multiply by <math>\frac{n!}{n!}</math> to obtain
 +
 +
<math>
 +
\sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}\sum^n_{k = 0}{n\choose k}\lambda_1^k\lambda_2^{n-k}
 +
</math>.
 +
 +
We can make use of the binomial formula to simplify this expression. Recall that the binomial formula is given by
 +
 +
<math>
 +
(a+b)^n = \sum^n_{k = 0}{n\choose k}a^k b^{n - k}
 +
</math>.
 +
 +
We use this to write
 +
 +
<math>.
 +
\sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}\cdot(\lambda_1 + \lambda_2)^n
 +
</math>
 +
 +
Putting this all together, we can finally write
 +
 +
<math>
 +
P(X = x | X+Y = n) = \frac{\frac{e^{-\lambda_1 + \lambda_2}}{n!}{n\choose x}\lambda_1^x\lambda_2^{n-x}}{\frac{e^{-\lambda_1 + \lambda_2}}{n!}\cdot(\lambda_1 + \lambda_2)^n} = {n\choose x}\frac{\lambda_1^x\lambda_2^{n-x}}{(\lambda_1 + \lambda_2)^n}
 +
</math>
 +
 +
and we are done.
 +
 +
===Similar Problem===
 +
 +
If <math>X</math> and <math>Y</math> are independent binomial random variables with success probabilities <math>p</math> and <math>q</math> respectively, find the probability mass function of <math>X</math> when <math>X + Y = k</math>. In addition, investigate what happens to this p.m.f. when <math>p = q</math>.
 
----
 
----
 
[[ECE-QE_CS1-2015|Back to QE CS question 1, August 2015]]
 
[[ECE-QE_CS1-2015|Back to QE CS question 1, August 2015]]
  
 
[[ECE_PhD_Qualifying_Exams|Back to ECE Qualifying Exams (QE) page]]
 
[[ECE_PhD_Qualifying_Exams|Back to ECE Qualifying Exams (QE) page]]

Latest revision as of 23:04, 31 January 2016


ECE Ph.D. Qualifying Exam

Communication, Networking, Signal and Image Processing (CS)

Question 1: Probability and Random Processes

August 2015


Solution 1

First of all, the conditional distribution can be written as:

$ P(X=x|X+Y=n) =\frac{P(X=x, X+Y=n)}{P(X+Y=n)} =\frac{P(X=x, Y=n-x)}{P(X+Y=n)} $

And

$ P(X=x, Y=n-x) =P(X=x)P(Y=n-x)\\ =\frac{e^{-\lambda_1}\lambda^x}{x!}\times \frac{e^{-\lambda_2}\lambda^(n-x)}{(n-x)!}\\ =\frac{e^{-(\lambda_1+\lambda_2)}}{x!} \left( \begin{array}{c} n\\x \end{array} \right) \lambda_1^x\lambda_2^{n-x} $

Also

$ P(X+Y=n) ={\sum_{k=0}^{k=n}P(X=k,Y=n-k)} ={\sum_{k=0}^{k=n}P(X=k)P(Y=n-k)}\\ =\frac{e^{-(\lambda_1+\lambda_2)}}{n!}\sum_{k=0}^{k=n} \left( \begin{array}{c} n\\k \end{array} \right) \lambda_1^k\lambda_2^{n-k}\\ =\frac{e^{-(\lambda_1+\lambda_2)}}{n!}(\lambda_1+\lambda_2)^n $

So, we get $ P(X=x|X+Y=n) = \left( \begin{array}{c} n\\k \end{array} \right) (\frac{\lambda_1}{\lambda_1+\lambda_2})^x(\frac{\lambda_2}{\lambda_1+\lambda_2})^{n-x} $

Solution 2

Let $ Z=X+Y $,

$ P_Z(k)=P_Z(z=k)=P_Z(x+y=k)\\ =\sum_{i=0}^{k}P(x=i)(y=k-i)=\sum_{i=0}^{k}\frac{\lambda_1^i e^{\lambda_1}}{i!}\cdot\frac{\lambda_2^{k-i}e^{-\lambda_2}}{(k-i)!} =e^{-\lambda_1-\lambda_2}\cdot \frac{(\lambda_1+\lambda_2)^k}{k!} $

Using $ (a+b)^k=\sum_{i=0}^{k}a^ib^{(k-i)}\cdot \frac{k!}{i!(k-i)!} $

Therefore,

$ P_{X|Z}(x=k|z=n)=\frac{P(x=k,z=n)}{P(z=n)}=\frac{P(x=k,x+y=n)}{P(z=n)}=\frac{P(x=k,y=n-k)}{P(z=n)}\\ =\frac{\lambda_1^k e^{-\lambda_1}}{k!}\frac{\lambda_2^{n-k} e^{-\lambda_2}}{(n-k)!}\frac{n!}{e^{-\lambda_1}e^{-\lambda_2}(\lambda_1+\lambda_2)^n} = \frac{\lambda_1^k \lambda_2^{n-k} }{(\lambda_1+\lambda_2)^n}\frac{n!}{k!(n-k)!} $

Solution 3

We will view this problem through the lens of Bayes' Theorem. As such, we can write the conditional distribution as

$ P(X = x | X+Y = n) = \frac{P(X = x, X+Y = n)}{P(X+Y = n)} = \frac{P(X = x, Y = n - X)}{\sum^n_{k = 0}P(X = k, Y = n - k)} $.

Since $ X $ and $ Y $ are independent, we can further write

$ P(X = x | X+Y = n) = \frac{P(X = x)P(Y = n - X)}{\sum^n_{k = 0}(P(X=k)P(Y = n-k))} $.

Now let us separate the above expression into numerator and denominator. Recalling that $ X $ and $ Y $ are independent Poisson r.v.s, the numerator is given by

$ P(X = x)P(Y = n - X) = \frac{e^{-\lambda_1}\lambda_1^x}{x!}\cdot\frac{e^{-\lambda_2}\lambda_2^{n-x}}{(n-x)!} $.

Multiplying the above by $ \frac{n!}{n!} $ gives

$ P(X = x)P(Y = n - X) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}{n\choose x}\lambda_1^x\lambda_2^{n-x} $.

Now let us examine the denominator. Again, we make use of the fact that $ X $ and $ Y $ are independent Poisson r.v.s to write

$ \sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \sum^n_{k = 0}\left(\frac{e^{-\lambda_1}\lambda_1^k}{k!}\frac{e^{-\lambda_2}\lambda_2^{n-k}}{(n-k)!}\right) $.

Again, we multiply by $ \frac{n!}{n!} $ to obtain

$ \sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}\sum^n_{k = 0}{n\choose k}\lambda_1^k\lambda_2^{n-k} $.

We can make use of the binomial formula to simplify this expression. Recall that the binomial formula is given by

$ (a+b)^n = \sum^n_{k = 0}{n\choose k}a^k b^{n - k} $.

We use this to write

$ . \sum^n_{k = 0}(P(X=k)P(Y = n-k)) = \frac{e^{-\lambda_1 + \lambda_2}}{n!}\cdot(\lambda_1 + \lambda_2)^n $

Putting this all together, we can finally write

$ P(X = x | X+Y = n) = \frac{\frac{e^{-\lambda_1 + \lambda_2}}{n!}{n\choose x}\lambda_1^x\lambda_2^{n-x}}{\frac{e^{-\lambda_1 + \lambda_2}}{n!}\cdot(\lambda_1 + \lambda_2)^n} = {n\choose x}\frac{\lambda_1^x\lambda_2^{n-x}}{(\lambda_1 + \lambda_2)^n} $

and we are done.

Similar Problem

If $ X $ and $ Y $ are independent binomial random variables with success probabilities $ p $ and $ q $ respectively, find the probability mass function of $ X $ when $ X + Y = k $. In addition, investigate what happens to this p.m.f. when $ p = q $.


Back to QE CS question 1, August 2015

Back to ECE Qualifying Exams (QE) page

Alumni Liaison

Meet a recent graduate heading to Sweden for a Postdoctorate.

Christine Berkesch